Prohibition of gender transition propaganda in Russian legislation: core provisions and problems of law enforcement - G. N. Komkova; E. N. Toguzaeva (Правоприменение)
The subject. Russian state regulation now extends to citizens’ lifestyles as a means of safeguarding traditional values. The purpose of the article is to analyze the legal framework surrounding the ban on gender transition propaganda in Russia and identifies shortcomings in this legal regulation.  The study is based on normative legal acts of the Russian Federation and research papers on this topic by both Russian and foreign scholars. The research methodology includes general and field-specific methods. The authors explored the issues associated with legal formalization of the ban on gender transition propaganda by applying general research methods (comparative legal research), field-specific methods (descriptive analysis, methods of comparative law), and general theoretical analysis methods (comparison, synthesis). Main results. The research highlights that the concept of “gender transition” is vaguely defined in current Russian legislation, resulting in a lack of uniform interpretation and arbitrary enforcement of the norms prohibiting gender transition propaganda.  Conclusions. The study emphasizes the need to establish criteria for gender transition to regulate the qualification of offenses related to gender transition propaganda. It also recommends amending the current norm in order to define criteria for classifying information as gender transition propaganda. To ensure uniformity in law enforcement practices, it is necessary to establish criteria for classifying information that “could prompt children to desire gender transition”. Currently, any information could potentially be perceived as belonging to this category (even kindergarten matinees where male educators dress up in female images, and vice versa, etc.). Information that encourages gender transition could include information about the benefits and painlessness of hormone therapy for gender transition, the advantages of surgical interventions for gender transition, the positive effects following gender transition, explicit calls for gender transition, etc. In the absence of clear criteria, there are concerns that decisions by law enforcement agencies to impose fines or restrict information on particular resources could be based solely based on the subjective views of individual officials regarding the legal category “gender transition.” This could lead to potential violations of citizens’ rights.